Nutrition Leadership Development: Capacity-Building Initiatives in Iran and the Middle-East Region Since 2009 - Davari, Azadeh; Rashidi, Arash; Baartmans, Jacques Antonius (Frontiers in Public Health, 2015)
Personal and organizational performance is determined by commitment and both technical and general competencies, including leadership skills. Academia, however, mainly targets technical aspects in its curricular programs. On the other hand, the inter-disciplinary and multi-sector nature of Nutrition necessitates high levels of collaboration between stakeholders. Leadership development is therefore required in Nutrition. This paper describes the endeavor made in Iran and the Middle-East region, aiming at building leadership capacity among nutrition professionals. The empowered human resource is expected to facilitate nutrition security at the national and regional levels. Since 2007, the development process of the initiative has begun through research, bench marking, and consultation. The “learning organizations,” “leadership from inside-out,” and “transformational leadership” frameworks have been employed as underpinning theories. Main topics have been self-awareness, effective communication, shared visioning, trust building, creativity, and motivating. Outbound team-building activities and coaching have also been included. The first workshop of the Iranian Food and Nutrition Leadership Program was held in 2009 in Tehran. The experience expanded to the region as the Middle-East Nutrition Leadership Program (MENLP). The Ph.D. Nutrition programs (at four leading Universities) and Iranian Nutrition Society have been taken as other opportunity windows to develop leadership competencies. Biannual Iranian nutrition congresses have been used as the main media for advocacy purposes. High-satisfaction rates obtained following each training activity. In short, the initiative on “nutrition leadership development” has received growing investment and positive feedback in Iran. Continuous improvement of the initiative, establishment of active alumni networks, building MENLP regional platform, and integrating a monitoring and evaluation system are required to increase the investment returns.